Pendekatan Integratif Pendidikan Tauhid dan Nilai-nilai Moderasi Beragama dalam Pembentukan Akhlak Terpuji - Danang Dwi Basuki (Intelektual)
Forming noble morals is Islamic education's primary goal, reflecting faith in Allah. However, challenges such as moral deviation, violence, and intolerance indicate the need for a holistic educational approach. This study analyzes the integration of monotheistic education and religious moderation values ​​in forming noble morals. Monotheism education is becoming a spiritual foundation, including Rububiyah, Uluhiyah, and Asma wa Sifat. Meanwhile, religious moderation values, such as tolerance (tasamuh), justice (i'tidal), and love of the homeland (al-muwathanah), provide social guidance in a multicultural society. This study uses a qualitative approach with a literature study design. The process is carried out through three stages: (1) identification of literature using relevant keywords, (2) selection of literature, and (3) thematic synthesis to reveal the relationship between monotheism education and religious moderation values. The study results indicate that the integration of monotheistic education and religious moderation values ​​can form noble morals relevant to modern challenges. For example, muraqabatullah (awareness of being watched by Allah) contains values ​​of improvement and exemplary behavior, while tawadhu (humility) strengthens values ​​of tolerance and anti-violence. This integration process can be implemented through a curriculum based on moderation values, experiential learning, and teacher training. In conclusion, the integrative approach forms tolerant religious individuals and contributes to social harmony. This paradigm reflects Islam as rahmatan lil 'alamin, as a solution to the challenges of character education in the era of diversity.